Motivation and burnout in elite athletes - Lemyre, P. N.; Gustafsson, H. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
While competing in sports large doses of training and high quality motivation are necessary to perform at the elite level (Gould, Dieffenbach, & Moffet, 2002; Lemyre, Roberts, & Stray-Gundersen, 2007). Unfortunately, some of the personal qualities necessary to achieve the highest levels of performance in sports are also risk factors for experiencing debilitating levels of exhaustion often leading to athlete burnout (Lemyre, Hall, & Roberts, 2008). When athletes suffer from burnout, they typically experience chronic fatigue, poor sleep patterns, and bouts of helplessness. They may also complain about episodes of depression related to their sport participation, and not surprisingly their performance is considerably impaired. Previous research findings have established a relationship between athlete burnout and levels of self-determined motivation (Cresswell & Eklund, 2005; Lemyre, Treasure, & Roberts, 2006; Raedeke, 1997). According to Self-Determined Theory (Deci & Ryan, 2000), on a continuum of self-determined motivation, intrinsic motivation is the most self-determined form of motivation and amotivation is the least self-determined form of motivation, while different levels of extrinsic motivation are found in between. These two forms of motivation are proposed to lie at the opposing ends of a self-determined continuum. Earlier burnout research has found that amotivation is positively and intrinsic motivation negatively associated with burnout (Cresswell & Eklund, 2005b; Raedeke & Smith, 2001). Furthermore, less self-determined motivation in the beginning of the season was associated with burnout at the end of the season in elite athletes (Lemyre et al., 2007). Lemyre and colleagues (Lemyre, Treasure, & Roberts, 2006) also found that motivation shifts along the self-determination continuum to less self-determined motivation during the season was associated with higher burnout susceptibility in swimmers. Thus, the aim of the current study was to investigate in parallel shifts in self-determined motivation and changes in burnout scores during the season of competition. Participants were 73 national ski academy students (F=42, M=31) competing in xc-skiing (N=44) and ski orienteering (N=29). Each week, for thirteen weeks, athletes answered to a translated version of the Athlete Burnout Questionnaires (ABQ; Raedeke & Smith, 2001) and the Situational Motivation Scale (SIMS; Guay, Vallerand, & Blanchard, 2000). Findings demonstrated a significant negative relationship between shifts in quality of motivation and changes in burnout scores over a 13 weeks period. Decrease in quality of motivation throughout the season is directly linked to an athlete`s susceptibility to experiencing feeling burned out. Furthermore, shifts in amotivation throughout the season were a very potent predictor of change in athlete propensity to burn out. Study findings suggest that monitoring quality of motivation of competitive athletes throughout the season may help steer athletes away from maladaptive sport participation outcomes such as exhaustion and burnout.